Can augers be used to blend diets on the farm? - S L Johnston; Robert H Hines; S L Traylor; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1995)
Growing/finishing gilts were fed two-, three-, four-, or five-phase diet regimens from 77 to 276 lb. The diets were mixed in either a conventional, horizontal ribbon mixer or a 9 ft auger. No interactions occurred among the mixer type and phase-feeding treatments. Pigs fed diets blended with the auger had similar ADG but slightly (4%) worse F/G compared to those fed diets mixed in the mixer. Finally, the three-phase regimen gave the lowest F/G and the lowest cost of gain.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Phase-Feeding; Finishing; Mixing